Effect of Different Shoe Lacing Pattern on Different Types of Foot in Recreational Runners - Rushikesh Rajendra Mangale, Amrutkuvar Rayjade (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: There has been an increase in the overall prevalence of obesity in India. There has been a 26% rise in the obesity among the young adults of India. At the same time, an awareness about fitness and health has also been on a rise in our country.Jogging and running have been on a rise in popularity among the youth of India. Heel-to-toe drop, styles of running, brand, fit and shoe lacing are some other factors that affect running. Out of these shoe lacing is one of the simplest factors to modify. It can be done by anybody and is an extremely cost effective measure. Methodology: An experimental study is being conducted with a sample size of 33 subject in karad. The population under study is Recreational runners age group of 20-40 years both male and female subjects. VAS and Foot Posture Index were the outcome measures used. Result: There was a significant effect of modifying shoe lacing patterns on FFI scores. (p=<0.001) There was also a significant effect on FPS (p <0.001) and FDS (p <0.001) subscales whereas there was no significant effect on ALS subscale (p >0.05). A significant decrease in pain was also noted. (p <0.05) Conclusion On the basis of the results of the study, it was concluded that there was a significant effect of modifying shoe lacing patterns on amateur runners.